Carbon dots as a smart nanoplatform for the blood‐brain barrier penetration and ischemic stroke therapy - Yanhan Huang; Xuan Hou; Haiping Zhao; Qi Kong; Xiayan Wang; Xiaokun Geng; Zaicheng Sun (Responsive Materials, 2026)
Abstract Ischemic stroke (IS) is one of the primary causes of global mortality and permanent neurological disability, and its clinical treatment is severely constrained by the intricate ischemic pathological cascade and the impermeable blood‐brain barrier (BBB). Cerebral ischemia and reperfusion trigger a series of pathological events including energy depletion, excitotoxicity, calcium overload, oxidative stress and neuroinflammation, accompanied by progressive BBB damage. These pathological processes exacerbate secondary brain injury and severely block the delivery of therapeutic drugs to lesion sites. Carbon dots (CDs), with their ultrasmall particle size, adjustable surface properties, excellent biocompatibility, inherent fluorescence feature and multi‐therapeutic bioactivity, have evolved into an advanced nanoplatform for targeted IS treatment. This review systematically outlines the structural characteristics and transport rules of the BBB, illustrates the pathological cascade of IS and its destructive effects on BBB integrity, and elaborates three major pathways for CDs to penetrate the BBB: passive diffusion, carrier‐mediated transport and endocytosis‐dependent transcytosis. It further highlights the therapeutic roles of CDs in IS‐associated pathological cascades, including reactive oxygen species elimination, mitochondrial protection, inflammasome modulation, programmed cell death suppression, and BBB integrity maintenance. In addition, iron‐associated oxidative stress modulation, mainly supported by ICH‐related models, is discussed as mechanistic evidence for stroke‐associated oxidative injury rather than as direct proof of IS therapy. Collectively, CDs serve as a flexible theranostic candidate for IS management. Nevertheless, more in‐depth research is required to clarify underlying mechanisms, optimize biosafety and promote future clinical translation.